A New Electrically Conducting Metal–Organic Framework Featuring U-Shaped cis-Dipyridyl Tetrathiafulvalene Ligands - Gordillo, Monica A.; Benavides, Paola A.; Spalding, Kaybriana; Saha, Sourav (Frontiers in Chemistry, 2021)
A new electrically conducting 3D metal-organic framework (MOF) with a unique architecture was synthesized using 1,2,4,5-tetrakis-(4-carboxyphenyl)benzene (TCPB) a redox-active cis-dipyridyl-tetrathiafulvalene (Z-DPTTF) ligand. While TCPB formed Zn2(COO)4 secondary building units (SBUs), instead of connecting the Zn2-paddlewheel SBUs located in different planes and forming a traditional pillared paddlewheel MOF, the U-shaped Z-DPTTF ligands bridged the neighboring SBUs formed by the same TCPB ligand like a sine-curve along the b axis that created a new sin-MOF architecture. The pristine sin-MOF displayed an intrinsic electrical conductivity of 1 × 10–8 S/m, which surged to 5 × 10–7 S/m after I2 doping due to partial oxidation of electron rich Z-DPTTF ligands that raised the charge-carrier concentration inside the framework. However, the conductivities of the pristine and I2-treated sin-MOFs were modest possibly because of large spatial distances between the ligands that prevented π-donor/acceptor charge-transfer interactions needed for effective through-space charge movement in 3D MOFs that lack through coordination-bond charge transport pathways.